Grant as a Special Type of budget Subsidies - S. V. Zapol’skii; E. M. Andreeva (Финансы: теория и практика, 2020)
The article provides the study of the Russian legislation on grants funded through the budget. The relevance of the research is due to the importance of grants in the development of human potential, stimulating innovative and other activities, as well as the lack of an overall estimate of budget legislation on grants by the scientific community. The aim of the article is to answer the following questions. First, whether state grant support in the Russian Federation is a special type of financing, or it is regulated by the general rules of budget or civil law. Second, whether the financial legislation on grants contributes to the economic and social development of Russia and to achieving grant objectives. Third, what proposals could increase the legal regulation of grant activities in the Russian Federation. The authors used the scientific methods of formal legal and comparative legal methods, generalization and modeling. They applied the method of comparative law to the legal regulation of grants in the European Union and to the attempt to transfer this positive experience to the Russian legal system. The modeling method helped the authors build a mocking mechanism for the legal regulation of grant activities in the Russian Federation. The formal logical method allowed for evaluating the current conceptual framework of grant support and making suggestions for improvement. Studying the regulatory legal acts and applying grant legislation by the authors resulted in the conclusion that the quality of legal support for grants in Russia is unsatisfactory. To improve the efficiency of legal regulation of grants, the authors propose to separate the concepts of “grants” and “budget subsidies”; to provide a separate chapter “Budget grants” in the Budget Code of the Russian Federation with the concept, procedure and grants funded through the budget. According to the authors, these proposals will be able to increase the effectiveness of state grant support in the Russian Federation.